Pharmacophore modeling, virtual screening and molecular docking of ATPase inhibitors of HSP70. (October 2017) - Sangeetha, K.; Sasikala, R.P.; Meena, K.S.
Graphical abstract: Highlights: Heat shock protein 70 is an effective anticancer target as it influences many signaling pathways. Key pharmacophore features required for ATPase inhibitory activity of HSP70 were identified by ligand based pharmacophore model. The identified most extrapolative pharmacophore model (hypotheses 8), consisted of four hydrogen bond acceptors. Three Phytochemical compounds and a synthetic drug were obtained as leads in the inhibition of ATPase activity of HSP70. Abstract: Heat shock protein 70 is an effective anticancer target as it influences many signaling pathways. Hence the study investigated the important pharmacophore feature required for ATPase inhibitors of HSP70 by generating a ligand based pharmacophore model followed by virtual based screening and subsequent validation by molecular docking in Discovery studio V4.0. The most extrapolative pharmacophore model (hypotheses 8) consisted of four hydrogen bond acceptors. Further validation by external test set prediction identified 200 hits from Mini Maybridge, Drug Diverse, SCPDB compounds and Phytochemicals. Consequently, the screened compounds were refined by rule of five, ADMET and molecular docking to retain the best competitive hits. Finally Phytochemical compounds Muricatetrocin B, Diacetylphiladelphicalactone C, Eleutheroside B and 5-(3-{[1-(benzylsulfonyl)piperidin-4-yl]amino}phenyl)- 4-bromo-3-(carboxymethoxy)thiophene-2-carboxylic acid were obtained as leads to inhibit the ATPase activity of HSP70 in our findings and thus can be proposed for further in vitro and in vivo evaluation.